HIGH TEMPERATURE SYNTHESIS OF POLYANILINE AS A COUNTER ELECTRODE IN DYE-SENSITIZED SOLAR CELL (DSSC) - NUR AMALINA NIM:10513012, AULIYA
Dye Sensitized Solar Cell is the third generation of Solar Cell that used dye as photo sensitizer in the device. The components that build DSSC device are TCO (Transparent Conductive Oxide), semiconductor film, dye, electrolyte, and counter electrode. Conductive polymers has been used as a DSSC counter electrode, such as polyaniline (PANI). Synthesis of PANI is usually held at low temperature to obtain high conductivity. In this study, the process of PANI synthesis is held at various relatively high temperature, and then characterize their properties and performances as counter electrodes in DSSC. The synthesis of PANI is held at 273, 298, 308, 318, 328, 338, and 348 K using rapid mixing method in ethylene glycol bath. The sample was characterized using FTIR-ATR spectroscopy, Raman Spectroscopy, UV-DRS Spectroscopy, Scanning Electron Microscope, and LCR meter. FTIR-ATR spectra shown the appearance of new peaks at 1038, 1211, and 1410 cm-1, represent the vibrational modes of phenazine structure at high temperature synthesis of PANI, fom 298 K to 348 K. In Raman Spectroscopy, it was observed the decrease of the intensity ratio of I1194/I1623 that related to the decrease of benzenoid ring that reached minimum at PANI 328 K and the decrease of the amount of secondary amine bond between the benzenoid ring. UV-DRS specroscopy provides the value of band gap energy of PANI, where PANI synthesized at 328 K has the highest band gap energy. The highest conductivity properties is found in PANI at 273 K, and tends to decrease and stablized at low conductivity for high temperature PANI. From the Scanning Electron Microscope, it is found that the morphology of PANI is globular shape at low temperature (273 K), while at high temperature it tends to form nanorod structure. The diameter of nanorod decreases with temperature until it reach the minimum at 338 K. The DSSC device with PANI counter electrode was tested with Solar Simulator, where resulted the highest efficiency is for PANI at 273 K (1,91%) due to its high conductivity. The lowest efficiency is found in DSSC device with PANI synthesized at 328 K (1,15%) due to its low conductivity and highest band gap energy. However, an increase in efficiency for PANI 338 K (1,71%) because its higher conductivity than PANI 328 K and smallest diameter of nanorod (67,63 nm). In this research it was found a local extreme condition of PANI at the potential surface energy for synthesis because of the thermal treatment that was given during the synthesis process, those condition was observed with the Raman spectra, band gap energy, conductivity, and the performance of the DSSC device of PANI synthesized at 328 K.